If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 + 6x = 11 Reorder the terms: -4 + 6x + 6x = 11 Combine like terms: 6x + 6x = 12x -4 + 12x = 11 Solving -4 + 12x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 12x = 11 + 4 Combine like terms: -4 + 4 = 0 0 + 12x = 11 + 4 12x = 11 + 4 Combine like terms: 11 + 4 = 15 12x = 15 Divide each side by '12'. x = 1.25 Simplifying x = 1.25
| s=zh-6zt^2 | | 0.4x+0.3y=1.2 | | 1=z/4 | | s=xh-6zt^2 | | 5=x+5-7x | | 8x-3x+9=24 | | y=-0.44x+248.33 | | -6x+33=9 | | -3-7=3x+7x-12x | | 7a-a=0 | | 6x-(4x+5)=4x-27 | | 80-(7x+8)=7(x+6)+x | | -w=-18 | | 0.3(x+100)+1.1x=79 | | 6y+7x=280 | | 4x+9-7x=18-14x+11x-9 | | -7/2(2b+4)+5(4b+2)=0 | | 17+6=3x | | -4x+10=-3(2x+2) | | 660/x=25/3 | | 0.4(x-4)=4.0 | | (x-3+9i)(x-3-9i)=0 | | 3y+8x=12 | | X*.03=28 | | 1/5(3x-4)=2/5 | | 1-x+4x+17=3x | | h([-3])=2x+4 | | y=0+(-4) | | 6x^2+12x=4 | | 4=-y | | 2x+6=8x-31 | | .85=200 |